Comparative Study and Transcriptomic Analysis on the Antifungal Mechanism of Ag Nanoparticles and Nanowires Against Trichosporon asahii - Han M; Xia Z; Zou Y; Hu P; Zhang M; Yang X; Ma MG; Yang R (International Journal of Nanomedicine)
Minna Han,1,2,* Zhikuan Xia,2,* Yuekun Zou,3 Ping Hu,4 Mingwang Zhang,5 Xin Yang,3 Ming-Guo Ma,6 Rongya Yang2 1Chinese PLA Medical School, Beijing, 100072, People’s Republic of China; 2Department of Dermatology, The Seventh Medical Center of PLA General Hospital, Beijing, 100072, People’s Republic of China; 3Department of Geriatrics, The Sixth Medical Center of PLA General Hospital, Beijing, 100072, People’s Republic of China; 4Department of Dermatology, Southern Medical Branch of PLA General Hospital, Beijing, 100072, People’s Republic of China; 5Department of Dermatology, Southwest Hospital, Army Medical University, Chongqing, People’s Republic of China; 6College of Materials Science and Technology, Beijing Forestry University, Beijing, 100083, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ming-Guo Ma; Rongya Yang, Email mg_ma@bjfu.edu.cn; yangrya@sina.comBackground: Silver nanomaterials have been widely proven to have antifungal effects against Trichosporon asahii. However, the antifungal mechanism of silver nanomaterials with different morphologies still needs to be explored.Methods: Herein, the antifungal effect of silver nanomaterials against fungus was comparative investigated via silver nanowires and silver nanoparticles with a similar size (30 nm).Results: The optimal antifungal concentration of silver nanowires is 6.24 μg/mL, meanwhile the antifungal concentration of silver nanoparticles is 100 μg/mL. The silver nanowires are significantly superior to the silver nanoparticles. SEM and TEM results indicated that both silver nanoparticles and silver nanowires showed significant morphological changes in the mycelium of the strain, compared with the control. The lower MFC value of silver nanowires indicates good sterilization effect and suitability for eradication treatment, which is slower than that of silver nanoparticles. Moreover, we also investigated the toxicological effects of silver nanoparticles and silver nanowires.Conclusion: We comparative studied and transcriptomic analyzed the antifungal mechanism of Ag nanoparticles and nanowires against Trichosporon asahii. The antifungal effects of silver nanowires were better than the silver nanoparticles, especially in the metabolic processes and oxidative phosphorylation. RNA sequencing results indicated that 15 key targets were selected for experimental verification to interpret the potential antifungal mechanism of Ag nanomaterials against fungus. This work proves that silver nanomaterials with different morphologies have potential applications in fungus therapy such as T. asahii.Keywords: Ag, nanoparticles, nanowires, fungus, antifungal mechanism, Trichosporon asahii, transcriptomics